Reindeer archaeology in northern Norway: A research excavation report from Gollevarre and Drag - Wickler, Stephen (Tromura, 2025)
This field report presents results from research excavations at the sites of Gollevarre in Tana, Finnmark and Drag in Tysfjord, Nordland. One of the main objectives was to obtain data for a Ph.D. project utilizing sedaDNA from cultural deposits and aDNA from reindeer bones to document the transition towards reindeer pastoralism. The excavations also provided insights into two medieval to early modern period settlements associated with reindeer exploitation from contrasting environments and cultural contexts within northern Norway.Gollevarre is a residential site occupied from the 12th to 17th century that had a primary focus on reindeer hunting utilizing nearby pitfall trapping systems. Multiple phases of settlement with overlapping turf house structures reflect intensive hunting-related seasonal use. A 2 x 1 m trench was excavated within a 16th to early 17th century refuse deposit associated with a nearby turf hut/house structure. The deposit consisted almost entirely of reindeer bone originating from disposal of household refuse and hearth maintenance. Although very few artifacts were recovered, fragments of modified reindeer bone and antler were documented throughout the deposit. A majority of the worked bone appears to reflect butchery activity that included extensive long bone splitting for marrow extraction. Zooarchaeological analysis of the reindeer assemblage revealed a skewing towards young individuals and high frequency of antler relative to contemporaneous Sámi dwelling sites in Finnmark. Non-reindeer faunal remains reveal a varied subsistence strategy including the presence of livestock (pig and sheep) and exploitation of wild game including fish, birds and mammals.The Drag settlement mound was first investigated as part of a research project on coastal Sámi farming settlements in Tysfjord. A 1.5 m2 unit excavated in 2009 documented a settlement sequence dated from the late 12th century into the 18th century. A 1 m2 unit was excavated in close proximity to the earlier excavation in 2024 and revealed two spatially distinct use zones in a cultural deposit spanning the 16th century. Two-thirds of the unit was occupied by boulders from a structural foundation wall. Slag from blacksmithing along with boat rivets and nails indicate specialized workshop use associated with the structure. The remainder of the unit reflects residential activity including waste disposal with significant quantities of charcoal and ash as well as highly fragmented bone dominated by domesticates, c. 60% burnt. The faunal assemblage as a whole is dominated by livestock but also includes small to medium sized wild mammals, birds, fish and fragments of worked whalebone. A majority of the five identified reindeer bone fragments are burnt. The presence of reindeer throughout the cultural deposit in the 2009 unit (n=20) was one of the main reasons for additional excavation in 2024.
Keywords: middelalder; medieval period; samisk reinjakt; sami reindeer exploitation; fangstanlegg; pitfall trapping; tamreindrift; reindeer pastoralism